What stage are low-income and middle-income countries (LMICs) at with patient safety curriculum implementation and what are the barriers to implementation? A two-stage cross-sectional study. Issue 6 (15th June 2017) - Ginsburg, Liane R; Dhingra-Kumar, Neelam; Donaldson, Liam J
Abstract : Objectives: The improvement of safety in healthcare worldwide depends in part on the knowledge, skills and attitudes of staff providing care. Greater patient safety content in health professional education and training programmes has been advocated internationally. While WHO Patient Safety Curriculum Guides (for Medical Schools and Multi-Professional Curricula) have been widely disseminated in low-income and middle-income countries (LMICs) over the last several years, little is known about patient safety curriculum implementation beyond high-income countries. The present study examines patient safety curriculum implementation in LMICs. Methods: Two cross-sectional surveys were carried out. First, 88 technical officers in Ministries of Health and WHO country offices were surveyed to identify the pattern of patient safety curricula at country level. A second survey followed that gathered information from 71 people in a position to provide institution-level perspectives on patient safety curriculum implementation. Results: The majority, 69% (30/44), of the countries were either considering whether to implement a patient safety curriculum or actively planning, rather than actually implementing, or embedding one. Most organisations recognised the need for patient safety education and training and felt a safety curriculum was compatible with the values of their organisation; however, important faculty-level barriers to patient safety curriculum implementation were identified. Key structural markers, such as dedicated financial resources and relevant assessment tools to evaluate trainees' patient safety knowledge and skills, were in place in fewer than half of organisations studied. Conclusions: Greater attention to patient safety curriculum implementation is needed. The barriers to patient safety curriculum implementation we identified in LMICs are not unique to these regions. We propose a framework to act as a global standard for patient safety curriculum implementation. Educating leaders through the system in order to embed patient safety culture in education and clinical settings is a critical first step.